PROBLEMATIKA PELAKSANAAN MUSYAWARAH RENCANA PEMBANGUNAN DESA (MUSRENBANG DESA) STUDI KASUS DESA RUMPA KECAMATAN MAPILLI - Nur Fitrah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This study aims to find out how the implementation of the Village development plan through Musrenbang in Rumpa Village, Mapilli District. This research is a field research using a qualitative approach. Methods of data collection through in-depth interviews with related sources and direct observation using data reduction techniques, data presentation and conclusion drawing. The results of the study show that the mechanism for implementing development planning in Rumpa Village has been running well and in accordance with regulations. But the level of participation needs to be improved, both public participation and government participation. Community participation in the form of thoughts, contributing ideas or ideas. Factors that hinder the level of community participation in musrenbang, namely the unpreparedness of the community due to their respective activities.